Factors Affecting Credit Card Usage Attitude: The Mediating Role of Transaction Behavior in Butwal Sub-Metropolitan City (The Lumbini Journal of Business and Economics, 2025)
Purpose: The study aims to investigate the mediating effect of Transaction Behavior on the relationship between Bank image, Credit Knowledge and credit card usage attitude. Likewise, It also explores the factors influencing individuals’ attitude towards the credit card. Methods: Descriptive and causal-comparative methods were applied, with statistical analyses such as Correlation and Regression. Data were collected from 384 credit card users in Butwal City through a snowball sampling method using a five-point Likert scale questionnaire. The sample included individuals from diverse occupations, income levels, and educational backgrounds. However, the study is limited to Butwal City and does not represent the entire Nepalese population.Results: The study found that Bank Image and Credit Knowledge are key factors influencing credit card usage attitude, mediated by Transaction Behavior. Transaction Behavior fully mediates the relationship between Bank Image and Credit Card usage attitude, while partially mediating the relationship between Credit Knowledge and Credit Card usage attitude. Conclusion: The study concludes that Bank image should invest in educational campaigns aimed at improving customer credit knowledge and focus on building a positive reputation and promoting trust to increase the transaction behavior of the customers